Effectiveness of a community-based water, sanitation, and hygiene (WASH) intervention in reduction of diarrhoea among under-five children: Evidence from a repeated cross-sectional study (2007–2015) in rural Bangladesh - Dey, Nepal C; Parvez, Mahmood; Islam, Mir Raihanul; Mistry, Sabuj K; Levine, David I (Science Direct, 2022)
This article was published in The Science Direct [© 2019 Elsevier GmbH. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/j.ijheh.2019.08.006 The Journal's website is at: https://www.sciencedirect.com/science/article/abs/pii/S1438463919304389?via%3Dihub